Eliminating illiteracy at the early twentieth century: a review of the history of the alphabet and scripture (Azerbaijan, Kazakhstan, Kyrgyzstan, Uzbekistan and Turkmenistan - Turgunov, Y.; Koch, K. (Journal of Oriental Studies, 2023)
The article will be about the writing and creation of the first alphabet books and educational tools for the eradication of illiteracy in the 20-40s of the 20th century in the field of Azerbaijan, Kazakhstan, Kyrgyzstan, Uzbekistan and Turkmenistan (hereinafter - the Countries). In addition, a review of the history of educational programs and the influence of fiction and its introduction into the education system was made in the state-wide measures to eliminate illiteracy. It is known that after the establishment of the Soviet Union, all activities of public education underwent a radical restructuring, paying attention to education and the construction of modern schools. In this direction, the work of related countries with similar concepts and views on education, eradication of illiteracy and school organization in the first half of the 20th century was differentiated. After the October Revolution, education became one of the most important areas of state policy. Scientific research work on pedagogy to completely eliminate the class division of the society was carried out widely and opinions were expressed on educational programs that were able to skillfully use the humanitarian sphere as an ideological tool. The place of literature in the countries as a tool in the literacy campaign, the foundations of its development as a folk, artistic subject (teaching, theory and methodology) were differentiated. The content of the educational program and the main goals, tasks and priorities that teachers should pay attention to during the lesson are given. Since teachers also need special methodical instructions, lesson plans, and advice in this direction, educational materials written by intellectuals of countries were studied in the educational campaign conducted in the Soviet Union. Among them, documents were given about educational tools and alphabet books for the elimination of illiteracy by the Kazakh writer Beimbet Mailin, whose methodical aspect has not been studied until now.